Reduksi Gas Metana dari Limbah Cair Kelapa Sawit Melalui Pembangkit Listrik Tenaga Biogas (Studi Kasus: PLTBg Tungkal Ulu Jambi) - Nisa, Jasmine Khairun; Wijayanti, Pini (Department of Urban and Regional Planning, Diponegoro University, 2023)
Most palm oil industries in Indonesia treat Palm Oil Mill Effluent (POME) by using an open lagoon system that releases methane gas emissions and potentially increases Greenhouse Gases (GHGs). Biogas Plant, a methane recovery project, becomes one measures to reduce such emissions. Biogas Plant projects support the government's target in reducing GHGs emissions and produces renewable energy. By focusing on the Tungkal Ulu Biogas, this study aims to (1) estimate the potential GHGs emissions prior the implementation of biogas project, (2) estimate the GHGs emissions reduction after the project implementation, and (3) to analyze the financial feasibility of the project. This study employes Clean Development Mechanism (CDM) method (i.e. the AMS III H) and cashflow analysis. The results showed that Tungkal Ulu Biogas project can reduce GHGs emissions and can benefit the company. The estimated GHGs emissions before Biogas Plant project from 106,267 m3 of POME are 44,767.80 t CO2e. The potential biogas emission reduction ranges from 66.64% to 74.26% during 2021-2030. Financial analysis indicates that the biogas project is feasible, at both low CER price and high CER price. The low CER results in NPV, BCR and IRR values of 18,55 billion rupiah, 1,19 and 11,46%, while high CER results in NPV, BCR and IRR values of 19,65 billion rupiah, 1.21 and 11,69%.